Southern Red Mite, Oligonychus ilicis (McGregor) (Arachnida: Acari: Tetranychidae) - Harold A. Denmark; W. C. Welbourn; Thomas R. Fasulo (EDIS)
EENY-376, a 4-page illustrated fact sheet by H.A. Denmark, W.C. Wellbourn, and T.R. Fasulo, was originally published as DPI Circular 79 and is included in the Featured Creatures series. It provides information on this important spider mite pest of broad-leaved evergreens, synonymy, distribution, description and biology, hosts, economic importance, management, and selected references. Published by the UF Department of Entomology and Nematology, July 2006.